PENGGUNAAN BAHASA PADA PAPAN NAMA TOKO DI KECAMATAN TAMPAN KOTA PEKANBARU - Neysha Verlanda; Charlina Charlina; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is about Language Usage on Store Name Board in Kecamatan Tampan Pekanbaru City. This study aims to describe what forms of store nameplate elements, the use of foreign languages, the use of word structure, and word selection. The method used in this research is prescriptive method with qualitative approach. Sources of data in this research is shop boards existing in kecamatan Tampan consisting of 4 kelurahan; Kelurahan Delima, Simpang Baru village, Tuah Karya village, and West Sidomulyo village. Technique of collecting data of this research that is by using technique of shooting and technique of record. The validity of the data is obtained by observational diligence techniques. The results of this study are as follows. First, the store nameplate element in Tampan sub-district was found in 11 elements. The elements are: 1) name, 2) store type, 3) product, 4) product information, 5) address, 6) zip code, 7) phone 8) slogan, 9) advertisement, 10) logo, 11) . The name element is an element required in the nameplate. This can be proven from each store nameplate data in Kecamatan Tampan found element name in it. Second, elements of kecamatan Tampan nameplate discourse are: 1) nameplate consisting of one element, 2) two elements, and 3) three elements. Third, the use of foreign languages on the shop name, whether it is in accordance with the rules of Law Number 24 Year 2009 or not. Fourth, the use of word structures on store nameplate in kecamatan Tampan. And fifth, the selection of appropriate and appropriate words on the shop name sign in Tampan district of Pekanbaru city.Keywords: Store Nameplate, Elements, Discourse, Foreign Language, Word Structure,Word Choice